Bidirectional and interactive effects of child temperament and parenting in early childhood on the trajectory of social anxiety in adolescence. Issue 3 (11th November 2021) - Lorenzo, Nicole E.; Novick, Danielle R.; Seddio, Kaylee; Degnan, Kathryn A.; Henderson, Heather A.; Almas, Alisa N.; Chronis‐Tuscano, Andrea; Fox, Nathan A.
Abstract: Introduction: Research suggests that certain parenting behaviors are best suited to promote optimal child development, depending on a child's distinctive temperamental presentation. This multimethod, longitudinal study examines the interactive effect of parenting and temperament in early childhood on the developmental trajectory of social anxiety in adolescence. Methods: Longitudinal growth modeling was used to examine the developmental trajectory of child social anxiety from age 9–15 and the interactive effect of parenting and child temperament at 36 months on the developmental trajectory of child social anxiety from age 9–15. Results: The slope of social anxiety from age 9–15 suggested a decrease in social anxiety throughout early adolescence. Furthermore, 36‐month behavioral inhibition (BI) predicted the trajectory of child social anxiety from age 9–15 when parents displayed low and high levels of dismissive and supportive parenting (at 36 months). Conclusions: Results support an interactive effect of infant temperament and parenting in early childhood (at 36 months) on the developmental trajectory of child social anxiety from age 9–15. Specifically, results suggest that engaging highly inhibited children with high supportive and low dismissive parenting may help reduce social anxiety over time in adolescence. Furthermore, parenting needs may differ for children high or low in BI to impact the developmental trajectory of social anxiety in adolescence, such that children who are high BI seem to benefit from low dismissive and high supportive parenting, and children who are low in BI seem to benefit more from high dismissive parenting.